2012
DOI: 10.1111/j.1532-5415.2012.03916.x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin, Other Antidiabetic Drugs, and Risk of Alzheimer's Disease: A Population‐Based Case–Control Study

Abstract: Long-term use of sulfonylureas, thiazolidinediones, or insulin was not associated with an altered risk of developing AD. There was a suggestion of a slightly higher risk of AD in long-term users of metformin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
242
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(261 citation statements)
references
References 32 publications
(53 reference statements)
9
242
1
2
Order By: Relevance
“…Metformin protects against neurological complications of type 2 diabetes mellitus, including cognitive impairment and cerebral vascular disease [263]. Recently, metformin has been used in a clinical trial for AD, and it is reported that this drug can produce beneficial effects in AD patients [264]. When administered with insulin, metformin provides significant neuroprotection in that A␤PP-A␤ levels including A␤PP-A␤ neuritic plaques, and oligomeric A␤PP-A␤-mediated downregulation of the insulin receptor are reduced [265].…”
Section: Metformin (Fig 3)mentioning
confidence: 99%
“…Metformin protects against neurological complications of type 2 diabetes mellitus, including cognitive impairment and cerebral vascular disease [263]. Recently, metformin has been used in a clinical trial for AD, and it is reported that this drug can produce beneficial effects in AD patients [264]. When administered with insulin, metformin provides significant neuroprotection in that A␤PP-A␤ levels including A␤PP-A␤ neuritic plaques, and oligomeric A␤PP-A␤-mediated downregulation of the insulin receptor are reduced [265].…”
Section: Metformin (Fig 3)mentioning
confidence: 99%
“…This links into the emerging hypothesis that AD should be classed as a third type of diabetes (115,116). However, reports are conflicting as to its effectiveness as a therapeutic intervention and the risk of developing AD (117,118). This may underlie the fact that the extent of metformin's molecular pharmacology is still under investigation (31,119,120).…”
Section: Relevance To Alzheimer's Diseasementioning
confidence: 99%
“…A case-control study based in the United Kingdom suggested that metformin may be associated with an increased risk of AD in longterm use [84], and treatment of mice with metformin has been shown to increase tau protein aggregation [85]. However, the same study does also show metformin to reduce tau phosphorylation, leading to the authors concluding that the benefits are mitigated by negative effects, rather than metformin having an overall detrimental effect [85].…”
Section: Metforminmentioning
confidence: 78%